Respuesta :

Answer:

Step 1 and step 2

Step-by-step explanation:

she has to subtract 30 not add 30.

2(3x+6)=3(x-10)

6x + 12 = 3x-30

6x +12 - 12 = 3x - 30 - 12

6x = 3x - 42

6x - 3x = 3x - 42 - 3x

3x = -42

3x/3 = -42/3

x = -14

Answer:

B

Step-by-step explanation:

Hey There!

So the first thing we're going to do is solve it and then compare it to Maya's steps to see where she made the mistake

2(3x+6)=3(x-10)

step 1 distribute the 2 to whats inside of the parenthesis (3x+6)

2*3x=6x

2*6=12

now we have

6x+12=3(x-10)

step 2 distribute 3 to what's inside of the parenthesis

3*x=3x

3*-10=-30

we're left with

6x+12=3x-30

step 3 add 30 to each side

12+30=42

now we have

6x+42=3x

step 4 subtract 6x from each side

3x-6x=-3x

now we have

-3x=42

step 5 divide each side by -3

42/-3=-14

so x = -14

now lets compare our steps to maya's

as we look at the steps we notice that she messes up on step 2

when distributing 3 to -10

she gets positive 30 but its supposed to be -30

so we can conclude that she mad a mistake from step 1 to step 2

therefore the second one is your answer

ACCESS MORE